Establishing the feasibility of a RCT comparing surgical versus non-surgical treatment for metacarpal shaft fractures in adults - Taha, Rowa (2024)
Background Metacarpal shaft fractures (MSF) are common traumatic injuries that predominantly affect young men of working age leading to functional impairment and consequently missed time off-work, leading to substantial societal costs. The aim of treatment is to restore hand function by maintaining the fracture in alignment until bone union, which is achieved either surgically using metalwork, or non-surgically by immobilisation in a splint or cast, with or without manipulation. Both treatment modalities require significant specialist resources, multiple hospital visits, and a period of rehabilitation of weeks to months, during which use of the hand is markedly restricted.